The Effect of Pores in Dual Nano Hydroxyapatite Coating on Thermally Oxidized Commercial Pure Titanium: Mechanical and Histological Evaluation - Dania F Mahmood; Salah A Mohammed (College of Dentistry/ University of Baghdad, 2016)
Background:In this study,TiO2 layer was thermally grown as a diffusion barrier on CP Ti substrate prior to electrophoretic deposition of HA coatings, to improve the coating's compatibility also macro and micro pores in nano Hydroxyapatite dual coatings were created and their effect on the bond strength between the bone and implant was evaluated. Materials and methods: Electrophoretic Deposition technique (EPD) was used to obtain coatings for each one of four types of Hydroxyapatite(HA)on CP Ti screws (micro HA, nano HA, dual nano HA with micro pores, dual nano HA with macro pores) where carbon particles used as fugitive material to be removed by thermal treatment to create porosity.For examination of the changes occurred on the substrate, SEM, SPM and XRD used, coatings characterized by XRD, SEM and interfacial shear strength measurements. Results:The results mentioned the formation of rutilenano TiO2 with, SEM showed that the size of pores in HA coatings corresponded to the size of carbon particles. Statistical analysis of the removal torque tests showed highest means of the single nano HA coating at 2 and 4 weeks implantation intervals. Histological analysisrevealed a faster reaction of bone and higher osteoblasts activity towards thermally oxidized CP Ti implants coated with single nano HA coating. Conclusion:Carbon particles as a fugitive material within nano HA coat produced porosity.Presence of pores ˃ 1µ in nano HA coats did not achieve highest removal torque values nor highest osteoblasts activity in 2 and 4 weeks implantation intervals. Keywords:Titanium, Thermal oxidization, Nano Hydroxyapatite, Coatings, porosity.